THE SUNNATULLAH OF POWER ROTATION IN Q.S. ALI IMRAN 140: A BALAGHAH AND FOURTH TURNING ANALYSIS - Zaimuddin; Luthviyah Romziana; Musholli; Sajid Fiestighfarilah (STKQ Al-Hikam Depok, 2026)
The rise and fall of power is a recurring pattern in human history. In Islam, this phenomenon is understood through the concept of sunnatullah, namely the divine laws that govern social and historical change. This study examines the concept of power rotation in Q.S. Al Imran [3]: 140 through a balaghah perspective and its dialogue with Fourth Turning Theory. Using a qualitative literature review, this study analyzes Qur’anic commentaries, balaghah literature, and works on historical cycles. The findings show that the phrase wa-tilka al-ayyamu nudawiluha bayna an-nas reflects a universal principle of power rotation as part of sunnatullah. The balaghah analysis highlights the continuity of historical change and the impermanence of worldly power. This study also identifies similarities with Fourth Turning Theory in viewing history as a recurring process, although sunnatullah is rooted in divine revelation, whereas Fourth Turning Theory is based on empirical observation. Therefore, sunnatullah provides a broader framework for understanding historical and civilizational change.